1999
DOI: 10.1139/w98-221
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of metal-resistant soil eubacteria by polymerase chain reaction - denaturing gradient gel electrophoresis with isolation of resistant strains

Abstract: Contamination of soils with heavy metal ions is a major problem on industrial and defense-related sites worldwide. The bioavailability and mobility of these contaminants is partially determined by the microbial biomass present at these sites. In this study, we have assessed the effect of the addition of a mixture of toxic metal salts on the prokaryotic community of microcosms consisting of sandy-loam soil using direct molecular analysis of the recoverable eubacterial 16S rDNA molecules by polymerase chain reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 40 publications
2
9
1
2
Order By: Relevance
“…Previous studies have documented that heavy‐metal contamination results in the reduction of bacterial diversity, biomass and metabolic activity [34–36]. In this study however, the presence of chromium could not be directly related to a low number of bacteria or to a reduction in diversity, evaluated by cultivable techniques.…”
Section: Discussioncontrasting
confidence: 67%
“…Previous studies have documented that heavy‐metal contamination results in the reduction of bacterial diversity, biomass and metabolic activity [34–36]. In this study however, the presence of chromium could not be directly related to a low number of bacteria or to a reduction in diversity, evaluated by cultivable techniques.…”
Section: Discussioncontrasting
confidence: 67%
“…Similarly, Kaplan and Kitts ( 2004 ) reported increase in the population of Flavobacterium and Pseudomonas at the end of fi rst 3 weeks of oil contamination thereafter their abundance decreased. Earlier Macnaughton et al ( 1999 ) reported similar observations for the coastal soils with experimental crude oil spill. Using phospholipid fatty acid (PLFA) analysis and 16S rDNA PCR-DGGE to monitor in situ microbial community structures they reported that contaminated plot was dominated by a -proteobacteria which were undetected for the uncontaminated plot.…”
Section: Diversity Of Petroleum Hydrocarbon Contaminated Soilssupporting
confidence: 76%
“…In other words, the community structure obtained from the same soil after enrichment using two different hydrocarbons could be different (Baek and Kim 2009 ) . Use of molecular genetic techniques like Denaturing Gradient Gel Electrophoresis (DGGE) and Terminal Restriction Fragment Length Polymorphism (T-RFLP) were proved to be benefi cial for judging the community structure of contaminated soil, which were independent of the ability of bacteria to grow in the culture media (Jung et al 2005 ;Kaplan and Kitts 2004 ;Macnaughton et al 1999 ) . Nutrient balance (C and N), pH and moisture content of soil were usually affected as a result of contamination by hydrocarbons (Bundy et al 2002 ) .…”
Section: Diversity Of Petroleum Hydrocarbon Contaminated Soilsmentioning
confidence: 99%
“…were commonly found at metal‐contaminated sites. In addition, according to Macnaughton et al [46], the major changes in the microbial community structure of metal‐treated microcosms consisted of the appearance of Acinetobacter sp. strains not detected in control microcosms.…”
Section: Discussionmentioning
confidence: 95%